2020
DOI: 10.3390/nu12010177
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Feeding Strategies in Pediatric Intestinal Failure

Abstract: Intestinal failure is defined as a critical reduction of the gut mass or function, below the minimum needed to absorb nutrients and fluids. The ultimate goal in intestinal failure is to promote bowel adaptation and reach enteral autonomy while a healthy growth and development is maintained. The condition is heterogeneous and complex. Therefore, recommendations for the type and duration of parenteral, enteral, and oral nutrition are variable, with the child’s age as an additional key factor. The aim of this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 109 publications
0
11
0
1
Order By: Relevance
“…To our knowledge, there is no trial aimed at verifying the best type of feeding after NEC resection. There is a large consensus reporting human milk as best choice of feeding for newborns and infants with SBS [ 44 , 156 , 158 , 159 , 160 , 161 ]. Breast milk is rich in proteins (immunoglobulin A), nucleotides, live cells, and growth factors together with other components such as lactoferrin and more than 100 different oligosaccarydes that can reinforce the immune system and enhance intestinal growth and adaptation [ 162 , 163 , 164 , 165 ].…”
Section: Best Nutrition Strategies To Enhance Intestinal Adaptatiomentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there is no trial aimed at verifying the best type of feeding after NEC resection. There is a large consensus reporting human milk as best choice of feeding for newborns and infants with SBS [ 44 , 156 , 158 , 159 , 160 , 161 ]. Breast milk is rich in proteins (immunoglobulin A), nucleotides, live cells, and growth factors together with other components such as lactoferrin and more than 100 different oligosaccarydes that can reinforce the immune system and enhance intestinal growth and adaptation [ 162 , 163 , 164 , 165 ].…”
Section: Best Nutrition Strategies To Enhance Intestinal Adaptatiomentioning
confidence: 99%
“…More recently, the use of cow’s preterm formula has been recommended in the absence of human milk [ 158 ], since it is characterized by higher caloric density and a composition based on lower lactose, higher MCT and long-chain triglycerides contents with the well-known advantages of these lipids [ 188 ]. The use of semi-elemental or elemental formula is suggested in those patients who are intolerant to conventional preterm/term formula [ 159 , 160 ].…”
Section: Best Nutrition Strategies To Enhance Intestinal Adaptatiomentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of feeding strategies, probably the recommendation with the most agreement among experts is that in infants with IF, human milk is considered to be the first choice [ 1 , 13 ]—beyond the amply documented health benefits of human milk, it is hypothesized that different components of breast milk may themselves potentialize intestinal adaptation (such as glutamine, growth hormone, and epidermal growth factor), while other components (such as nucleotides, immunoglobulin A, leucocytes, immunoglobulins, and antimicrobial peptides) provide important immunological support and promote a favorable microbiome environment [ 14 ]. Fortunately, we found that breast milk was the universal first choice reported when feeds were introduced in neonates/infants’ diet.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, SBS is divided into three phases: an acute phase, an adaptation and a recovery phase [ 17 ]. Successful bowel adaptation may lead to restoration of enteral autonomy.…”
Section: Foregut Manifestations and Their Pathophysiology In Intesmentioning
confidence: 99%